siRNA-mediated silencing of bFGF gene inhibits the proliferation, migration, and invasion of human pituitary adenoma cells - Kai Zhou; Yan-Dong Fan; Serick Duysenbi; Peng-Fei Wu; Zhao-Hai Feng; Zheng Qian; Ting-Rong Zhang (Tumor Biology)
Human pituitary adenoma is one of the most common intracranial tumors with an incidence as high as 16.7%. Recent evidence has hinted a relationship between growth factors of pituitary or hypothalamic origin and proliferation of human pituitary adenoma cells. This study explores the effects of small interfering RNA–mediated silencing of basic fibroblast growth factor gene on the proliferation, migration, and invasion of human pituitary adenoma cells. Human pituitary adenoma tissues were collected to obtain human pituitary adenoma cells. The basic fibroblast growth factor silencing interference plasmid was constructed, and the human pituitary adenoma cells were transfected and assigned as basic fibroblast growth factor–small interfering RNA, negative control–small interfering RNA, and blank groups. The quantitative real-time polymerase chain reaction and Western blotting were carried out to detect the expression of basic fibroblast growth factor, pituitary tumor transforming gene, vascular endothelial growth factor, cluster of differentiation 147, and matrix metalloproteinase 9. Cell Counting Kit-8 assay was conducted to observe cell proliferation at 0, 24, 48, and 72 h. Flow cytometry was used to determine cell cycle. Transwell and scratch test were applied to detect the invasion and migration of pituitary adenoma cells. Protein kinase C activity was detected. In comparison with the blank group, the basic fibroblast growth factor–small interfering RNA group showed reduced messenger RNA and protein expression of basic fibroblast growth factor, reduced cell viability at 24, 48, and 72 h, increased cells in G0/G1 stage, declined cells in S and G2/M stages, decreased number of cell migration, shortened migrating distance, reduced protein kinase C activity, and decreased expression of pituitary tumor transforming gene, vascular endothelial growth factor, cluster of differentiation 147, and matrix metalloproteinase 9. However, the negative control–small interfering RNA group had no evident differences in basic fibroblast growth factor expression, cell viability, cell cycle, number of cell migration, migrating distance, protein kinase C activity, and expression of pituitary tumor transforming gene, vascular endothelial growth factor, cluster of differentiation 147, and matrix metalloproteinase 9 compared with the blank group. The study provides evidence that small interfering RNA–mediated silencing of basic fibroblast growth factor gene inhibits the proliferation, migration, and invasion of human pituitary adenoma cells.